A noção de discriminação na obra de B.F.Skinner: uma análise de 1930 a 1937 - Feijóo, Merielle Totti (2014)
The present study acknowledges that Skinner s work is characterized by a process of formulation. Even the conceptions that are the underpinnings of his scientific proposal did not emerge completely formulated; those conceptions were refined and reformulated in different moments of his career. In order to characterize the path that led to the formulation of the arguably first elaborate notion of discrimination, 20 articles written by Skinner throughout 1930 and 1937 were investigated. Seven of these articles were analyzed directly whereas the other 13 articles were examined so that the context in which the study of discrimination was proposed could be described. The results were organized in accordance to the questions raised by Skinner throughout his investigation and in accordance to the answers he gave to those questions. Discussing the concept of induction was inevitable, since this process is thought to be central to the study of discrimination. It is suggested that the notion of discrimination might have initially emerged as a kind of refinement of conditioning